x(x+1)-3(x+1)=

Simple and best practice solution for x(x+1)-3(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+1)-3(x+1)= equation:


Simplifying
x(x + 1) + -3(x + 1) = 0

Reorder the terms:
x(1 + x) + -3(x + 1) = 0
(1 * x + x * x) + -3(x + 1) = 0
(1x + x2) + -3(x + 1) = 0

Reorder the terms:
1x + x2 + -3(1 + x) = 0
1x + x2 + (1 * -3 + x * -3) = 0
1x + x2 + (-3 + -3x) = 0

Reorder the terms:
-3 + 1x + -3x + x2 = 0

Combine like terms: 1x + -3x = -2x
-3 + -2x + x2 = 0

Solving
-3 + -2x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -1x)(3 + -1x) = 0

Subproblem 1

Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-1, 3}

See similar equations:

| 8x^2-4x+2=0 | | 9+2m=-3-4m | | x(x+3)-5(x+3)= | | 45=0.5(6+3) | | -9x=-27 | | 6(k-5)-(2k-4)=7k | | 9(y-7)=8+8y | | 6y+1-2y=8+3y+6 | | -9(n-6)=-8n-9 | | 4y+3y=6y+3 | | -3(4x-6)+8=-12x+26 | | 0.12(y-7)+0.04y=0.20y-0.9 | | 10x^3-8x^2+2x=0 | | 34X-25=18 | | -9(x-8)+2=74 | | 2(4x+7)-5=8x+9 | | -x+3=22 | | 15t^4-2t^2+78=0 | | n/2-9=-5 | | 30=48t-16t^2 | | 3(2x+35)+5(x+1)=u | | (15+9)x(22-5)= | | u/12-8=-8 | | 44=2(3.14) | | -8(t-4)-(t+1)=4 | | 6x-4=24x+2 | | 5(x+2)+7=17 | | r/2+6=5 | | 6(2x+33)+7(x+1)=u | | 3x^2+5=21 | | 50.2=2(3.14) | | 9(x-4)+4=-32 |

Equations solver categories